Improved Performance of CuFe2O4/rGO Nanohybrid as an Anode Material for Lithium-ion Batteries Prepared Via Facile One-step Method - Soomro, Sumair A.; Gul, Iftikhar Hussain; Naseer, Hashim; Marwat, Shafiqullah; Mujahid, Muhammad (Current Nanoscience, 2019)
Background: CuFe2O4 nanoparticles possess good electrochemical properties apart from their inadequate electronic conductivity and large volume variation. The resulting performance lag can be modified by the addition of conductive materials to form a composite. Hence, the properties of CuFe2O4/rGO nanohybrid are presented for application as anode material for lithium-ion batteries. Methods: The composites are synthesized through a facile one-step method of thermochemical reaction. The samples are characterized by X-ray diffraction (XRD), Scanning Electron Microscope (SEM), Fourier transform infrared spectroscopy (FTIR), Dielectric behavior and Galvanostatic charge-discharge test. Result & Conclusion: The XRD analysis confirmed the reduction of GO and formation of CuFe2O4/rGO composite, whereas FTIR results showed two major vibrational bands that correspond to spinel structure formation and attachment of rGO to CuFe2O4. The SEM images confirmed tethering of CuFe2O4 nanoparticles with rGO sheets. It was also observed that the formation of the nanohybrid of CuFe2O4 with rGO resulted in expected enhancement of the dielectric properties; dielectric constant and AC conductivity. At 100 Hz frequency, the dielectric constant of the composite with 15 wt. % of GO was 1.2705, which is higher than that of pure CuFe2O4 (3.5704). The parameters such as charge storage capacity and rate capability, which are reminiscent of battery performance were also enhanced with the increase of rGO content in the composite. Hence, a substantial enhancement of battery performance was depicted that projects the composite as a promising candidate for applications in electrode material for lithium-ion batteries.
Keywords: Fourier transforms infrared spectroscopy